The 1257 eruption in the pages of chroniclers and volcanologists (Studi di storia medioevale e di diplomatica - Nuova Serie, 2022)
The Samalas eruption of 1257 is ranked among the largest eruption in the last 7,000 years, as confirmed by sulphur deposition in ice cores of Arctic, Antarctica and Greenland and tree-ring records. In order to identify the spatial and temporal climate response to the Samalas eruption, volcanologists have used not only natural data but also contemporary documentary evidence, paying particular attention to medieval chronicles. This contribution focuses on the important contribution of narrative sources, also pointing out the problematic aspects related to the interpretation of these documentary sources. Starting from the Italian chronicles, the essay discusses the different meteorological and socio-economic impacts of the Samalas eruption in the wider European context.
Keywords: Chronicles; dendrochronology; volcano; Samalas; Middle Ages